B-1a cells mitigate radiation injury by protecting intestinal barrier integrity - Abe, Tomoki; Murao, Atsushi; Yamaga, Satoshi; Wang, Ping; Aziz, Monowar (Frontiers in Immunology, 2026)
IntroductionIonizing radiation causes severe gastrointestinal injury. B-1a cells, predominantly located in the peritoneal cavity (PerC), play a critical role in maintaining tissue homeostasis through the secretion of cytokines and natural antibodies. We aim to investigate the status of B-1a cells after irradiation, and their role in ameliorating radiation-induced intestinal injury.MethodsC57BL/6 mice were exposed to 12-Gy partial body irradiation (PBI) and B-1a cells in the PerC, spleen and bone marrow were determined by flow cytometry. After 24 hours of PBI, 5×105 B-1a cells were intraperitoneally administered in additional animals. Gut histology, intestinal barrier function, tissue injury markers, and TGF-β levels in PerC and gut tissue were assessed.ResultsIrradiation induced apoptosis in B-1a cells, resulting in depletion of B-1a cell numbers. Irradiation increased apoptotic cells in the crypts, decreased tight junction protein expression, and enhanced intestinal permeability. Adoptive transfer of B-1a cells significantly ameliorated these changes. The number of TGF-β-positive B-1a cells in PerC increased after B-1a cell transfer, accompanied by elevated TGF-β levels in both PerC and gut tissue.ConclusionWe demonstrated that B-1a cell numbers are significantly decreased following PBI and that B-1a cell treatment alleviates radiation-induced intestinal injury possibly via the increase in TGF-β production.